A sport-specific optimization approach to mental wellness for youth in low-income neighborhoods. (August 2020) - Donohue, Bradley; Gavrilova, Elena; Strong, Michelle; Allen, Daniel N.
Psychiatric disorders, particularly substance use disorders, are an impactful and highly prevalent public health concern in youth from low-income neighborhoods (YLINs). Indeed, prevention and intervention programs for mental health disorders that have evidenced improvements in youth from general population are not well integrated into community resources of YLINs and appear to be a poor fit for YLINs. Along this vein, experts have indicated there is an immediate need to empirically refine existing evidence-based mental health programs to be less stigmatizing, more culturally sensitive, relevant, and engaging for YLINs. To assist in addressing this need, we describe an innovative sport-specific optimization approach to mental wellness that is tailored for use in YLINs. Derived from Family Behavior Therapy, The Optimum Performance Programme in Sports (TOPPS) was developed to be implemented within the umbrella of well-established sport organizations that are accepted within low-income communities (e.g. YMCA, Boys & Girls Club) or primary and secondary school systems. TOPPS is designed to address both prevention and intervention of mental health disorders through a focus on overall wellness and sport performance, and incorporation of engagement methods, significant others, sport/physical education, and evidence-supported methods of addressing culture. Given the absence of sport-specific mental health intervention for youth, TOPPS may be appropriate in this population. However, formal evaluation of TOPPS in youth samples is warranted.